Experimental infection of H5N1 and H5N8 highly pathogenic avian influenza viruses in Northern Pintail (Anas acuta). Issue 5 (4th May 2018) - Kwon, J.‐H.; Lee, D.‐H.; Swayne, D. E.; Noh, J.‐Y.; Yuk, S.‐S.; Jeong, S.; Lee, S.‐H.; Woo, C.; Shin, J.‐H.; Song, C.‐S.
Summary: The wide geographic spread of Eurasian Goose/Guangdong lineage highly pathogenic avian influenza (HPAI) clade 2.3.4.4 viruses by wild birds is of great concern. In December 2014, an H5N8 HPAI clade 2.3.4.4 Group A (2.3.4.4A) virus was introduced to North America. Long‐distance migratory wild aquatic birds between East Asia and North America, such as Northern Pintail ( Anas acuta ), were strongly suspected of being a source of intercontinental transmission. In this study, we evaluated the pathogenicity, infectivity and transmissibility of an H5N8 HPAI clade 2.3.4.4A virus in Northern Pintails and compared the results to that of an H5N1 HPAI clade 2.3.2.1 virus. All of Northern Pintails infected with either H5N1 or H5N8 virus lacked clinical signs and mortality, but the H5N8 clade 2.3.4.4 virus was more efficient at replicating within and transmitting between Northern Pintails than the H5N1 clade 2.3.2.1 virus. The H5N8‐infected birds shed high titre of viruses from oropharynx and cloaca, which in the field supported virus transmission and spread. This study highlights the role of wild waterfowl in the intercontinental spread of some HPAI viruses. Migratory aquatic birds should be carefully monitored for the early detection of H5 clade 2.3.4.4 and other HPAI viruses.